Canakinumab leads to rapid reduction of neutrophilic inflammation and long-lasting response in Schnitzler syndrome - Bossart, Simon; Seyed Jafari, S. Morteza; Heidemeyer, Kristine; Yan, Kexiang; Feldmeyer, Laurence; Borradori, Luca; Yawalkar, Nikhil (Frontiers in Medicine, 2023)
IL-1-blocking therapies are effective in reducing disease severity and inflammation in Schnitzler syndrome. Here, we present a patient with Schnitzler syndrome treated successfully using canakinumab for over 10 years. Complete clinical response was associated with a decrease in dermal neutrophil number and expression of the pro-inflammatory cytokines IL-1β, IL-8, and IL-17 as assessed by immunohistochemical studies.